Model Epidemik Tuberkulosis Seir dengan Terapi pada Individu Terinfeksi - Alfensi Faruk (Faculty of Mathtmatics and Natural Sciences, 2016)
The spread of tuberculosis (TB) among individuals in the population can be described by the epidemic model, which is a mathematical model that divides the population into four subpopulations i.e. susceptible ( ), exposed ( ), infected ( ), and recovered ( ). The objective of this research is to build an epidemic model for TB transmission by involving total therapy rate ( ) in infected subpopulation. To illustrate the effects of , a numerical simulation with different values of was also carried out using R software. The results showed that the greater value of the total therapy rate, the decrease in the number of individuals in infected subpopulation became faster.